If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3u + -1(-7) = -4 Multiply -1 * -7 -3u + 7 = -4 Reorder the terms: 7 + -3u = -4 Solving 7 + -3u = -4 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3u = -4 + -7 Combine like terms: 7 + -7 = 0 0 + -3u = -4 + -7 -3u = -4 + -7 Combine like terms: -4 + -7 = -11 -3u = -11 Divide each side by '-3'. u = 3.666666667 Simplifying u = 3.666666667
| 4u+10=-5(u+7) | | 3x+x=2x-10 | | 3(9-3x)=27 | | 2(3a+9b)= | | 5.5(4.5b+6)=22.5+7b | | 8(y-3)=4y+4 | | 2x^3(x+1)=3x^2-(x-6) | | 2x-11=7x+6 | | 36=w+5w | | 5(8+7x)=390 | | -6x+4(x+8)=30 | | 5a-3whena=4 | | 12u-5u=56 | | F(8)=10-2x | | a^2+12a-47=0 | | 32=8v+5(v-4) | | 6(x+2)-2x=28 | | X-pie=pie | | 2(x+8)=-2x | | 2sin(-x)=0 | | 10(1+36)=20 | | x^4+x^2=684 | | -5.5+3.5(1-4s)=-20.5 | | tan63=34/x | | 15000=50*x^2/2 | | 3-(4x-2)=27 | | 3y^2-11y-16=0 | | 18=8v-4(v+8) | | (4x+3)(x)=320 | | 6n+3=3[-7n+1] | | (4x+5)(x)=400 | | 4+6[6-3n]=-5n-25 |